Personal Identity and Science: The genetic approach regarding the case of appropriated children during the most recent Argentinian dictatorship from a pluralistic perspective - Cordoba, Mariana (2019)
The philosophical problem of personal identity, the issue of finding the necessary and sufficient conditions for a past or future being to be a certain present being, has been treated by analytical metaphysics mostly. In this framework, plenty of references to thought experiments can be found, but they exhibit no connection to practical problems and scientific outcomes. Our purpose is to involve philosophy of science in that debate, since a genetic approach regarding identity can be considered supported by contemporary scientific knowledge. In order to do that, we will focus on the Argentinian case of the approximately 500 children who were appropriated during the most recent dictatorship (1976-1983). The appropriations deprived them, precisely, of their identities, but some of them managed to be recovered thanks to Abuelas de Plaza de Mayo (APM) and genetics. Our final purpose is to argue that a pluralistic perspective in philosophy of science, according to which values contribute to the very constitution of ontology science aims to describe and explain, will allow us to defend APM strategy but reject, at the same time, a reductive conception of identity.